Pendampingan Hukum dalam Menghadapi Era Bisnis Digital dan Persaingan Usaha Tidak Sehat bagi Pelaku UMKM di Surakarta - Hery Dwi Utomo (Jurnal Nusantara Berbakti, 2026)
The rise of the digital business era presents both opportunities and challenges for SME operators, particularly regarding legal aspects of business and unfair competition. This community service initiative aims to enhance the legal literacy and capacity of SME operators in Surakarta through educational and practical legal support. The methods employed included a pre-test to measure initial understanding, a legal needs assessment to identify participants’ legal requirements, the presentation of materials and interactive discussions as forms of intervention, and a post-test to evaluate improvements in understanding. The results of the activity demonstrated a significant improvement in participants’ legal knowledge and awareness, particularly regarding business contracts, digital transactions, and the risks of unfair competition. Furthermore, there was a shift in participants’ mindset, as they began to view the law as a strategic tool in running their businesses. Nevertheless, this initiative still faces challenges such as time constraints and the need for more intensive follow-up support. Consequently, legal support based on the actual needs of MSME operators has proven effective and requires continuous development to strengthen the competitiveness and legal protection of MSMEs in the digital age.